2021
DOI: 10.1001/jama.2021.15333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Varenicline With Nicotine Patch and of Extended Treatment Duration on Smoking Cessation

Abstract: IMPORTANCE Smoking cessation medications are routinely used in health care. Research suggests that combining varenicline with the nicotine patch, extending the duration of varenicline treatment, or both, may increase cessation effectiveness.OBJECTIVE To compare combinations of varenicline plus the nicotine or placebo patch vs combinations used for either 12 weeks (standard duration) or 24 weeks (extended duration).DESIGN, SETTINGS, AND PARTICIPANTS Double-blind, 2 × 2 factorial randomized clinical trial conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
2
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 32 publications
2
53
2
3
Order By: Relevance
“…According to the results of another study, it was reported that Varenicline in combination with nicotine replacement was more effective than Varenicline alone in the treatment of tobacco withdrawal (22). In the study of Baker et al, there was no significant difference in the prevalence of smoking cessation between those treated with varenicline and nicotine patches and those treated with varenicline monotherapy (23). Therefore, it appears that adding nicotine replacement therapy to varenicline treatment should be decided on Those with high nicotine addiction have difficulty quitting smoking compared to those with lower addiction levels (24).…”
Section: Discussionmentioning
confidence: 98%
“…According to the results of another study, it was reported that Varenicline in combination with nicotine replacement was more effective than Varenicline alone in the treatment of tobacco withdrawal (22). In the study of Baker et al, there was no significant difference in the prevalence of smoking cessation between those treated with varenicline and nicotine patches and those treated with varenicline monotherapy (23). Therefore, it appears that adding nicotine replacement therapy to varenicline treatment should be decided on Those with high nicotine addiction have difficulty quitting smoking compared to those with lower addiction levels (24).…”
Section: Discussionmentioning
confidence: 98%
“… 12 However, another recent study showed that adding nicotine patches to varenicline had little effect on abstinence rates (OR 0.99, 95% CI .87–1.12). 30 It is possible that fast-acting nicotine products—including gums, sprays, and e-cigarettes—are better at helping varenicline users remain abstinent, as they can satisfy momentary urges for nicotine. 31 Moreover, the behavior and sensory experience of using an e-cigarette is similar to that of smoking a cigarette, which could make e-cigarette more effective for smoking cessation than other nicotine products.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, another recent study showed that adding nicotine patches to varenicline had little effect on abstinence rates (OR 0.99, 95% CI 0.87-1.12). 30 It is possible that fast acting nicotine products — including gums, sprays, e-cigarettes — are better at helping varenicline users remain abstinent, as they can satisfy momentary urges for nicotine. 31…”
Section: Discussionmentioning
confidence: 99%